The influence of coal bottom ash as filler in asphalt mixture - Liew Siaw Ing, Nicole; Ng, Cui Ming; Muzamir, Hasan; Putra Jaya, Ramadhansyah; Ekarizan, Shaffie; Nordiana, Mashros; Mohamed, Abdullahi Ali (Trans Tech Publications, Switzerland, 2022)
The number of transport or vehicles on the road is increasing, which cause the road pavement or asphalt surface exposed to greater loading. Problems such as permanent deformation, cracking, fatigue, and skidding happened because of this repeated loading. There are many studies have been done to determine the suitable waste materials that can be used in order to improve resistance to rutting and fatigue cracking due to filler hardening and improve adhesion of filler to aggregate. The aim of this study is to investigate the effect of CBA on engineering properties of asphalt mixture. The different percentages of CBA (0%, 2%, 4% and 6%) were added to the asphalt mixture. The 60/70 penetration grade asphalt was used. The performance of the samples was evaluated through Marshall Stability, indirect tensile strength, resilient modulus, dynamic creep and image analysis. From the result obtained, there are significant effect comes from the addition of CBA. The result show that the addition of CBA in range of 2 to 4% produces the best outcomes for the density, stability, stiffness and flow while 6% for indirect tensile strength, dynamic creep and resilient modulus. Thus, it can conclude that the existence of CBA can enhance the performance of asphalt mix.